ANALISIS MODEL KEPEMIMPINAN KEPALA DESA DALAM PENGEMBANGAN POTENSI DESA - Joi Setiawan; Bambang Tri Harsanto; Sukarso Sukarso (Program Magister Administrasi Publik, Fakultas Ilmu Sosial dan Politik, Universitas Jenderal Soedirman, 2016)
The type of research is a quantitative with survey approach. This research was conducted in Banjarnegara Regency. The data collection was conducted using questionnaires and documentation. Data analysis technique used is regression analysis to examine the effect of independent variables on the dependent variable. The results showed: Supportive Leadership and leadership Directive does not have a significant influence on the development potential of the village. Partisipative Leadership has a significant influence on the development potential of the village. That is the better application of Partisipative Leadership, it will also increase the development potential of the village. This means that the development potential of the village to get the full support of the entire village government representatives including the village and community institutions. Achievement-oriented leadership has a significant influence on the development potential of the village. That is the better application of achievement oriented leadership, it will also increase the development potential of the village. This means that the development potential of the village need to get the full support of the village chief. Partisipative Leadership is the most influential factor or has the most dominant influence compared to other leadership styles that give effect to the potential development of the village in Banjarnegara Regency. Keywords: Achievement Oriented Leadership, Directive leadership, Partisipative Leadership, Supportive Leadership. Increase of Local Potential Resources.